Influence of the COVID-19 Pandemic on Exports in Türkiye: Evidence from ARDL Model - Zaim Reha Yaşar (İktisat Politikası Araştırmaları Dergisi)
Türkiye is a country in which the COVID-19 pandemic has deeply affected export performance. The aim of this paper is to analyse the impact of the COVID-19 pandemic on Turkish export performance using different variables indicating the severity of the COVID-19 effects. The effect of COVID-19 on Türkiye’s export performance is empirically analysed with the ARDL approach by employing time series data covering the 2013:q1-2022:q1 period. The estimation results of the six models indicate that COVID-19 does not affect Turkish export performance in the long term, whereas its lagged variables have negative and significant effects in the short term. Foreign income has positive and statistically significant effects on export volumes in both the short and long term. The exchange rate significantly and negatively affects export flows in both the short and long term. The results of this paper are robust against different types of COVID-19 proxies. COVID-19 has negative effects on exports in the short run for Türkiye’s economy. The results indicate that policymakers should consider the lagged effects of variables in addition to the current version. The findings also show the recommendation that short- and long-run estimations should be conducted to determine the short- and long-run relations.